TINGKAT KEEFEKTIFAN LACTOPEROXIDASE SYSTEM (LPS) UNTUK MEMPERPANJANG LAMA SIMPAN SUSU SEGAR - Fitriyono Ayustaningwarno; Bernadetha Soedarini; Ita Sulistyawati; Gijsbert Peter Eijhusen (JURNAL AGROTEKNOLOGI, 2007)
Fresh milk is high risk food since it is susceptible to microorganism spoilage. Without appropriate handling, fresh milk will spoil in short time. Lactoperoxidase is an enzyme that in its nature in milk was not an antibacterial, but can be activated to be an antibacterial. The method is used to activate lactoperoxide for milk preservation known as lactoperoxidase system (LPS). This experiment aims to identify LPS effectiveness in two different temperatures. Fresh milk sample, obtained from Nyatnyono Village, Ungaran Central of Java. Fresh milk storage duration was compared between milk without LPS in room temperature (25-28oC), milk without LPS in refrigerator temperature (5-10oC), milk with LPS in room temperature, and milk with LPS in refrigerator temperature. The total bacterial cells (TPC), Salmonella count ,and Eschericia coli count, and pH were examined. Total bacteria in all treatments were increased, except in LPS at refrigerator temperature that have storage duration until 20 hours. In the all of treatments, Salmonella counts were increased rapidly except in milk with LPS at refrigerator temperature that have storage duration until 8 hours. However, E. coli could growth well in all treatments during storage. The pH value can be kept below 6 in all treatments, except in milk without LPS at room temperature. Keywords: effectiveness of lactoperoxidase system, storage duration